Revealing the anti-inflammatory activity of Euphorbia hirta extract: transcriptomic and nitric oxide production analysis in LPS-Induced RAW 264.7 cells - Dinia Rizqi Dwijayanti; Muhammad Hermawan Widyananda; Feri Eko Hermanto; Aris Soewondo; Mufidah Afiyanti; Nashi Widodo (Food and Agricultural Immunology)
Excessive production of nitric oxide (NO) dan pro-inflammatory cytokines can lead to tissue damage and chronic inflammation. Euphorbia hirta presents an interesting opportunity for plant-derived anti-inflammatory agents as it contains a range of compounds which have demonstrated anti-inflammatory effects. This study investigates the anti-inflammatory properties of E. hirta extract on gene expression and NO production in LPS-treated RAW 264.7 cells. The results demonstrate that E. hirta extracts effectively suppress NO production in RAW 264.7 cells. Furthermore, the extract inhibits iNOS protein expression and reduces the expression of pro-inflammatory cytokines TNF-α and IL−12. RNA sequencing revealed significant alterations in gene expression, including 167 upregulated and 56 downregulated genes-related inflammation pathways. The study concludes that E. hirta extract possesses anti-inflammatory activity by modulating gene expression and inhibiting NO production in LPS-treated RAW 264.7 cells. The extract influences genes associated with inflammation signalling pathways, including cytokine signalling, NF-κB, iNOS and JAK-STAT pathways.